Desenvolvimento de um sistema técnico para aplicação automatizada de produtos líquidos em cultivos agrícolas - Bayer, Fernando Mariano (2019)
The growing world demand for food and energy has required a steady increase in agricultural production. This must be achieved through the development of technologies that allow for increased productivity combined with sustainable production. Precision agriculture and the automation of production processes have proven to be an important tool to achieve these goals. In this scenario it is necessary to introduce automated processes also in the research branches, allowing systems integration with the new information technologies, ensuring agility and precision in the collection and processing of test data and field tests. The present work aims to develop an automated sprayer for experiments in small plots. Requirements were defined as obtaining a safe system, simple operation, good accuracy and reliability. Based on this information was developed the design, construction of a prototype and final validation of the system. It will perform the data recording, providing a detailed report of the application process. Validation tests have shown that the system has met the previously defined requirements and has advantages over the currently used manual process.